2014
DOI: 10.4317/medoral.19114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dentaport ZX and Raypex 6 electronic apex locators: An in vivo study

Abstract: Introduction: Raypex 6 is an electronic apex locator (EAL) that has not yet been tested in vivo. The purpose of this in vivo study was to compare the accuracy of two EALs: the Dentaport ZX and the Raypex 6. Material and Methods: The study involved 36 straight single-rooted teeth. A 10-K file was advanced until the EAL detected the major foramen. The file was fixed in a replaceable pattern of light-cured composite. The apical part of each canal was trimmed to expose the file tip. The distances from the file ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
4
14
2
1
Order By: Relevance
“…Saraswathi [20] found similar results with Raypex 5. Differently from our findings, other study showed high accuracy with Raypex 6 [21], even when compared with conventional radiographs [22,23]. demonstrated that RootOR showed an accuracy of 86.7%.…”
Section: Resultscontrasting
confidence: 99%
“…Saraswathi [20] found similar results with Raypex 5. Differently from our findings, other study showed high accuracy with Raypex 6 [21], even when compared with conventional radiographs [22,23]. demonstrated that RootOR showed an accuracy of 86.7%.…”
Section: Resultscontrasting
confidence: 99%
“…The Root ZX series EALs showed a tendency to underestimate WL in some previous studies. [24,[27][28][29] These results differ from those obtained in the present study and some previous studies in which long measurements were made rather than short measurements. [11,12,17,30] Furthermore, high standard deviations were observed for the DentaPort ZX and SIROEndo Pocket in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings correspond to the results of a similar study, which found 95% or 93.4% accuracy for the Root ZX mini, depending on the selected file size . The results of the present study for the Raypex 6 were 90% and 95% measurement accuracy (± 0.5 mm), which is comparable to results with 90.41% and slightly better than the 88.22% result in another study . At 89.3% and 91.5% (± 0.5 mm), the EDU also exhibited an accuracy in detecting the apical foramen similar to other studies that reported 90% or 86.2% and 84.8% depending on file size .…”
Section: Discussionsupporting
confidence: 90%
“…Comparative studies on the accuracy of electrometric length determination and cone‐beam computed tomography (CBCT) have been published in increasing numbers, with results ranging from superiority of the electrometric measurement ( in vitro ) or a very good correlation of the results to equally good results ( in vivo ) . The accuracy of apex locators in determining the length of the major foramen (± 0.5 mm) is currently between 32.1% and 88.22%, depending on the device and the irrigant used . There are also several additional factors that adversely affect the results or even prevent reliable measurements .…”
Section: Introductionmentioning
confidence: 99%